Adolescent students' attitude towards premarital sex and unwanted pregnancy - Bhatta, Dharma Nand; Koirala, AK; Jha, N (Health Renaissance, 2013)
Background: In Nepal, as in other Asian countries, the issue on sexuality still remains a taboo. Despite this, there are increasing numbers of sexual activities reported among Nepalese adolescents. Objective: To know the attitude towards premarital sex and unwanted pregnancy of adolescent students. Methods: Three higher secondary schools were randomly selected and students of those schools were taken purposively with structured self administered questionnaires. Cross-sectional study design was adopted and significance levels were observed with 95% confidence level (pd.0.05 for significant). Descriptive and inferential analyses were done with the sample size 324. Results: Among the total respondents, 32.4% mentioned premarital sex is appropriate and 25% had premarital sex. One third (33.3%) of the total respondents. peers were taking alcohol, 37.7% had smoking habit and 8.3% had drug dependency. Among the respondents having experience of premarital sex, 61.7% had the first sex at the age of mean ± SD 17.72 ± 0.849 years. Among the boys 32.6% and among the girls 13.7% had the premarital sexual intercourse. Majority of boys and girls had first sex with girl friend and boy friend respectively. Among the total respondents who had premarital sex, 16% faced the problem of unwanted pregnancy. Among them, 53.8% managed the unwanted pregnancy by surgical abortion procedure and remaining 46.2% managed by taking medicine (medical abortion). Conclusion: Sexual and reproductive health of the adolescents is now growing concern for many developing countries due to increasing trend in sexual activities and unwanted pregnancies among the adolescents. Health Renaissance, January-April 2013; Vol. 11 No.1; 145-149 DOI: http://dx.doi.org/10.3126/hren.v11i2.8222